2018
DOI: 10.1177/0267658318775143
|View full text |Cite
|
Sign up to set email alerts
|

Lexical accent perception in highly-proficient L2 Japanese learners: The roles of language-specific experience and domain-general resources

Abstract: This article reports empirical findings on the roles of domain-general resources and language-specific experience in the second language (L2) acquisition of Japanese lexical pitch accent. Sixty-one advanced-proficiency L2 Japanese learners from two first languages (L1s), Mandarin Chinese and Korean, identified and categorized Japanese nouns embedded in short sentences in two aurally-presented tasks. Mixed effects models showed that although the tonal-language Chinese group outperformed non-tonal Korean speaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(94 reference statements)
1
11
0
Order By: Relevance
“…Goss and Tamaoka (2015) found that F0 discrimination ability accounted for a significant amount of variation in L1 Japanese listeners' perception of accent patterns, suggesting that even native listeners, with their well-established lexical store, rely on a domain-general perceptual capacity to perform certain listening tasks. However, at the advanced L2 proficiency levels, F0 discrimination was no longer a significant predictor of accent perception or was a least masked by the stronger predictor of Japanese lexical knowledge (Goss & Tamaoka, 2019). This contradictory pattern of findings-that musicianship and acoustic sensitivity relate to perceptual ability in both inexperienced learners and L1 listeners, but not in advanced learners-calls for further data on the role of this capacity in L2 lexical accent learning.…”
Section: Auditory Processing Abilitymentioning
confidence: 87%
See 4 more Smart Citations
“…Goss and Tamaoka (2015) found that F0 discrimination ability accounted for a significant amount of variation in L1 Japanese listeners' perception of accent patterns, suggesting that even native listeners, with their well-established lexical store, rely on a domain-general perceptual capacity to perform certain listening tasks. However, at the advanced L2 proficiency levels, F0 discrimination was no longer a significant predictor of accent perception or was a least masked by the stronger predictor of Japanese lexical knowledge (Goss & Tamaoka, 2019). This contradictory pattern of findings-that musicianship and acoustic sensitivity relate to perceptual ability in both inexperienced learners and L1 listeners, but not in advanced learners-calls for further data on the role of this capacity in L2 lexical accent learning.…”
Section: Auditory Processing Abilitymentioning
confidence: 87%
“…There is also a large class of unaccented words in Japanese that do not contain an F0 fall (Ito & Mester, 2016). L1 Japanese listeners, and even highly proficient L2 learners with large vocabularies (Goss & Tamaoka, 2019), are assumed to represent these accent patterns as lexically relevant information in their mental lexicon (Cutler & Otake, 1999).…”
Section: Lexical Pitch Accent In L2 Japanesementioning
confidence: 99%
See 3 more Smart Citations